The Health Cadres Assistance Program Through the Establishment of Complementary Feeding Corners as a Preventive Effort to Address Child Nutrition Issues - Kostania, Gita; Cahyani, Desy Dwi; Rosmalawati, Ni Wayan Dwi; Nurmayanti, Rani (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Malnutrition, including wasting and stunting, is a significant public health problem in Indonesia. In Malang Regency, the prevalence of stunting reaches 23%, exceeding the national and WHO thresholds. Petungsewu Village faces challenges related to inadequate nutritional intake among toddlers. Proper complementary feeding is crucial in preventing malnutrition. Empowering cadres through structured training and mentoring enhances maternal knowledge and feeding practices, supporting efforts to reduce malnutrition rates. This community service program aimed to strengthen the capacity of cadres in Petungsewu Village by establishing the Complementary Feeding Corner. The program, implemented from February to November 2024, involved training and mentoring in the preparation and management of complementary feeding using locally sourced ingredients. A total of 32 cadres participated. The evaluation results indicated a significant improvement in cadres' knowledge and skills. After training, 90.63% of cadres achieved a